ISOLATION OF PHOSPHATE SOLUBILIZING FUNGI IN SOIL FROM KANCHANABURI, THAILAND - Nopparat, Chalit; Jatupornpipat, Marisa; Rittiboon, Aree (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2007)
Phosphorus replenishment, particularly in smallholder agriculture, remains a challenge as it is mainly fertilizer dependent. While the user of soluble mineral phosphate fertilizers is the obvious best means to combat phosphate deficiency in soil, they were limited by high cost of fertilizers and availability at farmer’s level. This research is to isolate and select phosphate solubilizing soil fungi from Kanchanaburi area. One hundred and forty five fungi isolates were incubated on Pikovskaya agar supplemented with 0.003% w/v rose bengal, isolates which gave the high ratio of clear zone were selected. Four fungal strains out of 30 strains, i.e., SA07P3332, SA22P3406, SA14P2418 and SA19P2120 solubilized tricalcium phosphate and showed the highest available phosphate in liquid medium. The available phosphate were 3.010, 2.993, 2.749 and 2.632 mg P2O5 ml-1, respectively. All of the fungal strains are fast growing black colonies on potato dextrose agar with distinctive conidial heads characterized as Aspergillus sp. Their phosphatase enzyme activities were 0.029-0.102 unit ml-1 min-1 for acid phosphatase (pH 6.5) and 0.022-0.102 unit ml-1 min-1 for alkaline phosphatase (pH 11). Keywords: phosphate solubilizing fungi, phosphatase and available phosphate Corresponding author: E-mail: kjmarisa@gmail.com